Evaluation of dental socket healing after using of porous titanium granules: Histologic and histomorphometric assessment in dogs - Mohammad Tavakoli; Ahmad Moghareabed; Tayebeh Farsam; Fatemeh Mashhadi Abbas; Hamid Badrian; Navid Khalighinejad (Wolters Kluwer Medknow Publications, 2012)
Background: Different methods have been suggested to preserve bone architecture following traumatic events such as teeth extraction. The purpose of the study was to histologically and histomorphometrically evaluate the dental socket healing after applying porous titanium granules (PTG) in dogs. Materials and Methods: Four healthy male dogs were involved in the present 6-weeks experimental animal study. Three sockets were surgically created in each side of dog's mandible. One of the sockets in one side was randomly filled by PTG and covered by a resorbable membrane (Tigran + membrane group). Another socket was left unfilled and just covered by the same membrane (membrane group) and the last one was left unfilled and uncovered as the control group. The dogs were killed at two time intervals (2 weeks and 6 weeks, two dogs at each time point). All samples were histologically evaluated under an optical microscope for a new bone formation. Data were analyzed by SPSS ver. 16 and Kruskal-Wallis and Mann-Whitney tests were used to compare data in different groups (α = 0.05). Results: There was a significant difference between the Tigran + membrane and the control group in 2 and 6 weeks in the mean amount of total regenerated bone (P < 0.05). The mean amounts of woven, lamellar, and total regenerated bone showed significant differences between 2 weeks and 6 weeks for all three groups (P < 0.05). Conclusions: It can be assumed that the use of Tigran bone substitute with membrane can promote the bone regeneration in bone defects.